Exploring Dropouts as Challenges in Higher Education in Nepal: A Comprehensive Review - Ghimire, Mayanath; Mishra, A.K.; Bolar , Jaishree (International Research Journal of MMC, 2024)
The purpose of this study is to analyse the dropout rate of campus level of students in Nepal. The researchers adopted the process of scientific review as a meta-synthesis to analyse the dropout rate of the campus level students. An in-depth archival analysis followed by an intensive review would be strategies adopted during the scientific review. Secondary data was gathered by searching Google for scholarly publications and articles published between 2001 and 2024. The students want part-time jobs during the study. Such opportunities are less common in Nepal. The research study revealed that Nepali students gave their first priority to Australia, Canada, the USA, and Europe for their higher studies. After finishing their studies, they desired to stay there due to their job security. They applied for green card and permanently stayed there. On the other hand, Nepal lost young and skilled manpower who stayed abroad as immigrants. The study reveals that government can prevent brain-drain by proving financial assistance and employment opportunities to bachelor’s level students. The Nepalese government should make appropriate policy to retain its young workforce. Otherwise, its adverse impact will be seen soon.